The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.3382/japr.2012-00559
|View full text |Cite
|
Sign up to set email alerts
|

Palatability of tannin-rich sericea lespedeza fed to broilers

Abstract: As parasites become resistant to available anthelmintics, new methods of control are needed. New drugs take a long time to develop in addition to being expensive; therefore, there is increasing interest in finding and using natural alternatives. Additionally, natural remedies are needed for the organic sector because synthetic drugs are not allowed and birds with outdoor access are likely to encounter parasites. Sericea lespedeza [SL; Lespedeza cuneata (Dum. Cours.) G.Don.] is a common perennial legume found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The decrease in bird performance corroborates the results reported by Moyle et al (2012) who used diets containing tannin from the lespedeza plant and observed a decrease in bird weight and an increase in FI with worsening FCR.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The decrease in bird performance corroborates the results reported by Moyle et al (2012) who used diets containing tannin from the lespedeza plant and observed a decrease in bird weight and an increase in FI with worsening FCR.…”
Section: Resultssupporting
confidence: 90%
“…The use of acacia tannin provided a quadratic effect (P < 0.05) on the relative weight of the liver at 42 days of age, with the highest weight of this organ observed with the inclusion of 896.75 g ton -1 of tannin. Moyle et al (2012) observed that when using 20 % sericea lespedeza, a tannin rich grass, the relative liver weight increased compared to the control diet. The liver can be affected by the toxic effect of tannin, since it is responsible for coagulation factors, and also since it is the primary source of several serological metabolites including urea, albumin, and glucose (SILVA et al, 2011).…”
Section: Resultsmentioning
confidence: 96%
“…They also reported that a concentration of up to 2.6 g kg -1 of tannins in the diet did not significantly affect the performance of broiler chickens, but in this experiment, it was possible to note a reduction in broiler performance with the maximum tannin concentration of 0.9 g kg -1 . Moyle et al (2012) observed that when fed on increasing levels of Sericea lespedeza, a grass rich in tannin, poultry decreased in weight in the second and third week of life, and showed an increase in FI and consequently worsening FCR. This decline in performance is related to ingredients with low nutrient levels in the diet, such as tannins.…”
Section: Resultsmentioning
confidence: 98%
“…Calcium homeostasis is influenced by the production of parathormone, calcitonin and renal hydrolase for the activation of cholecalciferol, which acts on intestinal absorption and metabolic utilization (NELSON;COX, 2008). According to Macari et al (2002), this homeostatic mechanism has an important function in preventing excessive absorption or toxicity of Ca in birds.…”
Section: Resultsmentioning
confidence: 99%
“…Of further concern is that it is expected that the incidence of dental caries and periodontal disease will continue to increase as a result of the growing intake of sugars in the diet, tobacco use, and inadequate exposure to fluorides, and lack of access to dental care [22]. Increasing antibiotic resistance has promoted interest in the therapeutic use of non-conventional or alternative medicines and plant extracts [13,[23][24][25][26]. It has been shown that naturally occurring biocides are effective in inactivating a variety of microorganisms by affecting multiple target sites and are therefore less prone to development of resistance compared to conventional antibiotics targeting specific bacterial sites [27,28].…”
Section: Discussionmentioning
confidence: 99%